Development of Historical Tourism by Community Based Tourism Management Processes. - thanavut, sucheera; Laksameetanasarn, Suphaporn; Nhukheaw, Ekarach; Viriya, Phungpornphat; Prechanun, Chidchanok (Journal of Management Science Nakhonratchasima University, 2026)
This study employs a mixed-methods research approach. Quantitative data were collected from 35 participants, While qualitative data was gathered from 12 Key informants. Data analysis was conducted using statistical software and content analysis. The findings revealed that the majority of respondents were female, under 30 years of age, had a monthly income of less than 15,000 Baht. Were students and actively participated in community activities. The Qualitative findings identified three primary development guidelines: Raising Awareness, There should be a concerted effort to instill a sense of preservation and conservation among local youth. This can be achieved by encouraging them to study historical information and culture significance in order to facilitate knowledge transfer to tourists and the general public. Product and Service development: Unique local products reflecting the identity of the tourist destination such as keychains, bookmarks, notebooks, and postcards, should be developed as valuable community resources. Service development should include, traditional Thai massage, herbal compress, foot massage, and herbal foot baths to align with the identity of "Prasat Mueang Kao" or Arokayasala during the reign of King Jayavarman VII. Historical Tourism development: Community stories and historical narratives should be creatively communicated to tourists through activities such as short plays, traditional dance performances, and events organized on significant occasion. Furthermore, the local identity of the historical tourist destination should be promoted through traditional weaving, local cuisine, traditional desserts, and locally crafted souvenirs. These initiatives aim to enhance historical tourism through community-based learning activities, offered in the form of one-day or two-day tour programs.